Optic nerve head changes in acute central serous chorioretinopathy: Implications for glaucoma risk - Esma Ecem Ersoy; Ebubekir Durmuş (Photodiagnosis and Photodynamic Therapy)
Objective: Imaging techniques have demonstrated changes in the choroid and retina in acute central serous chorioretinopathy (CSCR), but the effects on the optic nerve head (ONH) remain unclear. This study investigates ONH structural changes in acute CSCR using enhanced deep imaging optical coherence tomography (EDI-OCT). Methods: A prospective cohort study included 51 acute CSCR patients and 51 healthy controls aged 18–65 years. Patients had symptoms for less than three months, with no prior treatment or ocular pathology. Participants with refractive errors of ±6D spherical or less and ±3D cylindrical or less were included, while with optic nerve/choroidal conditions, corticosteroid use, systemic diseases like sleep apnea, and media opacities were excluded. Comprehensive eye exams and EDI-OCT were performed to evaluate retinal, choroidal, and ONH parameters. Results: The mean subfoveal choroidal thickness (SFCT) (434.51±95.45 µm vs. 289.55±87.21 µm) and peripapillary choroidal thickness (PPCT) (282.12±79.14 µm vs. 180.79±53.99 µm) were significantly higher in the CSCR group compared to controls (p < 0.001 for both). Retinal nerve fiber layer (RNFL) (107.14±15.15 µm vs. 101.06±14.31 µm, p = 0.04) and lamina cribrosa thickness (LCT) (307.14±63.83 µm vs. 200.04±54.23 µm, p < 0.001) were significantly higher, while anterior laminar depth (ALD) and Bruch's membran opening-minimum rim width (BMO-MRW) were significantly lower in the acute CSCR. Conclusion: In acute CSCR, increased SFCT is accompanied by a corresponding rise in PPCT, leading to significant ONH structural changes and enhanced blood flow, potentially offering glaucoma protection. However, further research is needed to explore the long-term effects of chronic CSCR on choriocapillaris ischemia and optic nerve.